Hubungan Antara Resiliensi dengan Penerimaan Ibu yang Memiliki Anak Usia Dini Penyandang Down Syndrome - Jenny Augta Schalwyk; Eli Prasetyo (Psychopreneur Journal, 2026)
Down syndrome is a genetic condition that causes physical and mental delays due to abnormal development of chromosomes. For mothers, treating down syndrome in early childhood requires more attention because it is not an easy thing, beside that mothers have other tasks. In this case, treating down syndrome children require patience and desire from mothers. Patience and desire in mothers is a form of acceptance against children with down syndrome. This research aims to determine whether there is a correlation between resilience and mother’s acceptance who have children with down syndrome using quantitative methods. The research involved 60 mothers who have children with down syndrome and used a purposive sampling method. The measuring instrument used in the research was the Resilience Scale and Mother’s Acceptance Scale. The results of hypothesis testing through Kendall's Tau-B correlation analysis show a value of p = .000 (p < .05) and r = .434, so it can be concluded that there is a correlation between resilience and mother’s acceptance who have children with down syndrome.